Ophiuroidea das regiões Antártica e Subantártica: 1. Sobre três espécies de Gorgonocephalidae e Ophiacanthidae - Monteiro, Ana Maria Gouveia [UNESP]; Tommasi, Luiz Roberto (Universidade de São Paulo (USP), Instituto Oceanográfico, 1983)
É estudada a distribuição geográfica e a variação de caracteres morfológicos de três espécies de ofiuroides (OpiLacantha antartica, Astrotoma agassizzi e Gorgonecephalus chilensis) das regiões Antártica e Subantãrtica. São também apresentadas observações sobre biologia reprodutiva.

The geographical distribution and the variation of morphological characters of three (Gorgonecephalus chilensis, Astroma agassizii, Ophiacantha antartica) from the Antarctic and Subantarctic regions are studied. Observations on reproductive biology are presented.
Ophiuroidea from Antarctic and subantarctic regions: 1. on three species of Gorgonocephalidae and Ophiacanthidae
Keywords: Distribuição geográfica; Morfologia; Ofiuróides; Reprodução biológica; Região antártica; Geographical distribution; Morphology; Ophiuroids; Reproduction (biology); Antarctic region